The Effect of Levofloxacin Addition on the Outcome of Tuberculous Meningitis Patients: A Systematic Review and Meta-analysis - Lorisna Hardiknastia Damastiwi; Saiful Hidayat; Paulus Stephen Pulung Aditya Nugraha Sembiring (Department of Neurology Faculty of Medicine Universitas Sebelas Maret, 2024)
Background: Tuberculous meningitis (TBM) is one of tuberculosis's deadliest extra-pulmonary manifestations. Although early initiation of anti-tuberculosis drugs can reduce mortality and morbidity, poor blood-brain barrier penetration hampered their effectiveness. Levofloxacin is an anti-tuberculosis drug with good BBB penetration. Objective: We aim to explore whether levofloxacin addition to the TBM patients’ regimen has a potential benefit to improve their outcomes. Methods: The literature search was done on PubMed, Google Scholar, and ProQuest databases without publication date limits to identify studies investigating the effect of augmenting levofloxacin in the outcome of TBM patients. The primary outcome of this study was to analyze the impact of these regimens in decreasing the risk of death and neurological deficit. The articles were collected using the PRISMA diagram, critically appraised using PICO analysis, then the data were analyzed using Review Manager 5.4.1 software with a Fixed Effect Model. The results were expressed as odds ratio (OR). Results: Four randomized controlled trials with a total of 930 patients were identified. Two trials compared the effectiveness of levofloxacin addition only, whereas the other two used the regimen containing the increased dose of rifampicin alongside levofloxacin addition. Based on the analysis, neither levofloxacin addition only nor increasing rifampicin dose with levofloxacin addition had a significant impact on the mortality of TBM patients (OR=0.55; 95% CI 0.19-1.59; p=0.27, OR=1.01; 95% CI 0.74-1.36; p=0.97, respectively). Conclusion: Additional Levofloxacin on TBM treatment shows no significant improvement in patient mortality. Routine levofloxacin use in TBM is discouraged due to limited evidence.